The Influence Of Work Life Balance And Burnout On Job Satisfaction With Work Culture As An Intervening Variable At TVRI Stations - Nur Chairany Senjayu; Rahmad Bahagia (Jurnal Ekonomi, 2024)
Abstract TVRI North Sumatra first broadcast on December 28 1970 as TVRI Medan. This station is the second TVRI regional station to be established after TVRI Yogyakarta, which was formed more than five years earlier. Effective human resource management is very important for the continuity and success of a company. Corporations really want all their employees to have a significant level of job satisfaction. Work- life balance refers to the balance between the allocation of time and energy for work and the allocation of time for business. Another obstacle to achieving professional happiness is fatigue. Burnout may arise as a result of severe stress related to work. External factors that influence student satisfaction in doing work outside campus are determined by the level of support provided by the campus. This research uses a quantitative type of research using a cross-sectional study design. which aims to explore the relationship between the variables Work-Life Balance, Burnout, Work Culture, and Job Satisfaction in an organization